MUTU SENSORIS DAN MIKROBIOLOGIS COOKIES DARI CAMPURAN TEPUNG INSTAN JAGUNG KUNING DAN TEMPE - Susi Desminarti; Ermiati Ermiati; Mutia Elida (Jurnal Sains dan Teknologi Pangan, 2023)
Cookies are pastries that are crunchy, thin, and usually small in size. Corn and tempeh are foods that have been known to have functional properties. The purpose of this study was to determine the effect of the use of yellow corn flour with tempeh flour and on sensory characteristics and microbiological quality and to determine the most preferred cookie formulation by consumers. The formulation of cookies is to replace wheat flour with flour mixed with yellow corn and tempeh as much as 40% (B), 50% (C), 60% (D), 80% (E) and the formulation uses 100% flour as a control (A). Sensory characteristics observed include color, aroma, taste, texture, overall appearance. Based on the hedonic test, the substitution of wheat flour with instant yellow corn flour and tempeh flour as much as 40% has sensory properties that are closest to control A. The panelist likes it. The total microbial and total yeast content for all treatments were below the safe threshold for consumption Keywords: cookies functional, dates grits, yellow corn flour, dan tempe flour